The Role of the K-loss Coefficients Applied to Finned Tube Heat Exchanger Design - Lázaro Canizalez-Dávalos; Edilberto Murrieta-Luna; Victor J. Cruz-Delgado; Claudia Y. Valero-Luna; Alan Bañuelos-Frías (Chemical Engineering Transactions)
This article presents a modified method for designing finned tube heat exchangers based on calculating the K-loss coefficients on the side tube. Besides, a CFD simulation is set up to analyse pressure drop and flow distribution on the staggered tubes. The performance of finned tube heat exchangers depends on several factors, including the number of staggered tubes, tube length, fin pitch, tube pitch, and fin area. Finned tube heat exchangers improve thermal effectiveness, particularly when dealing with gas and liquid fluids. The staggered tube arrangement complicates the prediction of pressure drop on the tube side. Also, two head pipes configure the inlet and outlet flows. The equations for determining pressure drop assume uniform velocity and constant flow distribution throughout the equipment. These correlations do not include the frictional pressure drop caused by the 180° bends welded on the tubes. In addition, equations fail to include the fluid distribution in each parallel circuit of tubes. Considering heat exchanger components as hydraulic resistances in both series and parallel configurations, an equation was developed to sum the K-loss coefficients for the tube bundle, bends, inlet pipe, and outlet pipe. From the hydraulic design results and considering that all tubes distribute water at 93 °C, the next stage consists of the thermal heat exchanger design based on the NTU method to heat air at 50 – 60 ºC. The heat exchanger design is evaluated by comparing the results with an experimental case study. This includes water flow distribution, heat transfer area, hot and cold outlet fluid temperatures, pressure drop and CFD numerical results.